The teachers ability and response concerning Spatial Orientation. (February 2020) - Johar, R; Zubainur, C M; Khairunnisak, C; Elizar, E; Suhartati; Syukri, M
Abstract: This paper examined the profile of secondary school mathematics teachers about spatial orientation. Participants in this study were 20 secondary school teachers who participated in a mathematics learning workshop related to designing a floor plan. Usually, the teacher conducts weekly or monthly meetings through the group of mathematics teachers in Banda Aceh, Indonesia. The teachers were given a spatial orientation test before and after the workshop, four of them were interviewed. The data obtained were analysed descriptively. The results showed that there is an increase in the teacher spatial orientation ability score after the workshop. The findings also reported some teachers had difficulty in solving the spatial orientation problems because they were not familiar with determining the direction. In addition, most teachers agreed that spatial test is necessary for the students despite their concern about the time constraint. Thus, we suggest utilizing technology to overcome such an issue.